A study of employability skills: from the employers and youth perspectives / Nur Amalina Holidi and Noor Aslinda Abu Seman - Holidi, Nur Amalina; Abu Seman, Noor Aslinda (Faculty of Business and Management, 2023)
The issues of skills mismatched among the youth and employers appear to be very intense in Malaysia. The unemployed youth are actively seeking jobs and trying to fulfill the criteria needed by employers to get hired. However, many failed to fulfill the requirements due to skills mismatched. This situation does not show that the supply meets the demand in terms of youth employment and job vacancies. Thus, this study aimed to explore the perceptions of employers and youth regarding the employability skills required by the youth to secure employment and any disparities in their perceptions. This study was a cross-sectional survey research design and employed a quantitative method by distributing a set of questionnaires that adapted from the Secretary's Commission on Achieving Necessary Skills (SCANS) to two groups of respondents which are employers (n=375) and youth (n=384) in Batu Pahat, Johor. Descriptive analyses and Mann-Whitney U tests were used to analyze the data. The findings showed significant differences in the perception levels of employers and youth regarding most of the employability skills assessed except for Basic Skills. The results from this study can be used to enhance the understanding of employability skills as well as to be the guidelines for policy-making decisions to find mutual expectations and reduce the expectation gaps between these two groups.